Factors Influencing Traffic Accidents Among the Elderly in Northern Iran: A Qualitative Content Analysis - Nima Faghirpour; Enayatollah Homaie Rad; Leila Kouchakinejad; Zahra Mohtasham Amiri (Bulletin of Emergency and Trauma)
Objective: The study aimed to explore experts’ perspectives on the factors contributing to accidents involving the elderly in Guilan, Iran. Methods: This qualitative study employed conventional content analysis with an inductive approach in 2024. Fourteen experts from Guilan (Iran) were purposefully selected. Data were collected through individual face-to-face interviews using a semi-structured interview guide containing open-ended questions, which was developed through an expert panel discussion. All stages of data analysis were performed manually following the Graneheim and Lundman’s approach. Results: Three main categories, 10 subcategories, and 29 key codes were identified. The “Individual Factors” category had six subcategories: physical abilities, psychological factors, traffic literacy, cultural attitudes, and Individual needs. The “Environmental Factors” had two subcategories: road and traffic infrastructure, and weather conditions. The “Policy-making” category consisted of three sub-categories: transportation safety, healthcare system, and public education. Conclusion: To reduce damages from elderly-related accidents, preventive measures should focus on improving health services, enhancing traffic education, and addressing specific behavioral and cultural factors. Additionally, enhancing infrastructure, designing age-appropriate vehicles, and implementing targeted policies could significantly mitigate accident risks among this population.